A point mutation in MC06g1112 encoding FLOWERING LOCUS T decreases the first flower node in bitter gourd (Momordica charantia L.) - Zhong, Jian; Cui, Junjie; Miao, Mingjun; Hu, Fang; Dong, Jichi; Liu, Jia; Zhong, Chunfeng; Cheng, Jiaowen; Hu, Kailin (Frontiers in Plant Science, 2023)
In Cucurbitaceae crops, the first flower node (FFN) is an important agronomic trait which can impact the onset of maturity, the production of female flowers, and yield. However, the gene responsible for regulating FFN in bitter gourd is unknown. Here, we used a gynoecious line (S156G) with low FFN as the female parent and a monoecious line (K8-201) with high FFN as the male parent to obtain F1 and F2 generations. Genetic analysis indicated that the low FFN trait was incompletely dominant over the high FFN trait. A major quantitative trait locus (QTL)-Mcffn and four minor effect QTLs-Mcffn1.1, Mcffn1.2, Mcffn1.3, and Mcffn1.4 were detected by whole-genome re-sequencing-based QTL mapping in the S156G×K8-201 F2 population (n=234) cultivated in autumn 2019. The Mcffn locus was further supported by molecular marker-based QTL mapping in three S156G×K8-201 F2 populations planted in autumn 2019 (n=234), autumn 2020 (n=192), and spring 2022 (n=205). Then, the Mcffn locus was fine-mapped into a 77.98-kb physical region on pseudochromosome MC06 using a large S156G×K8-201 F2 population (n=2,402). MC06g1112, which is a homolog of FLOWERING LOCUS T (FT), was considered as the most likely Mcffn candidate gene according to both expression and sequence variation analyses between parental lines. A point mutation (C277T) in MC06g1112, which results in a P93S amino acid mutation between parental lines, may be responsible for decreasing FFN in bitter gourd. Our findings provide a helpful resource for the molecular marker-assisted selective breeding of bitter gourd.